The Relevance of Ibn Qudamah's Thought on the Transfer of Family Waqf Assets in the Contemporary Era: A Normative Study of Islamic Family Law - Nuri Safitri; Nugraha Adi Saputra; Ermanita Permatasari; Naser Ali Abdulghani; Sayyid Abdurrohman; Rizki Anisa Fitria (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose - The practice of family waqf is basically in accordance with sharia and has a legal basis in fiqh. However, its existence is debated because it is considered less productive and its allocation is limited to the family of the waqif, so in various Muslim countries this waqf practice has been abolished. This study aims to determine the relevance and flexibility of Ibn Qudamah's thoughts on waqf towards the transfer of family waqf into productive waqf intended for the general public. This study is framed in contemporary Islamic family law studies that emphasize the social role of the family in society. Methods - This research is a descriptive qualitative library research. Primary data is taken from the book “Al-Mughni” by Ibn Qudamah and supplemented by secondary data in the form of books, journal articles, proceedings articles, theses, theses, and other literature related to the transfer of waqf. The data was collected using the documentation method and analyzed using content analysis techniques. Findings - Based on Ibn Qudamah's thinking, the transfer of the function of family waqf assets is possible if there is no shar'i impediment. Switching the function of family waqf into productive waqf intended for the general public must be done through deliberation between the nadzir, waqif, and also family members. In the perspective of contemporary Islamic family law, the transfer of family waqf functions is one of the efforts to strengthen the social role of the family in the community. This is one of the indicators of a maslahat family and is in accordance with the principle of hifz al-maal (protecting property). Research limitations - This research is limited to normative studies that relate Ibn Qudamah's thoughts with waqf practices in Indonesian society. Given this limitation, future research is expected to continue the findings in this study by using an empirical approach that integrates with other sciences. Originality - This research is expected to be a normative and practical reference to the practice of family waqf function transfer in Indonesia. This is because not many studies have examined this issue, especially from the perspective of contemporary Islamic family law.